EFFECTS OF CORYNEBACTERIUM PSEUDOTUBERCULOSIS ON SHEEP KIDNEYS - Hussain, Majid N. (The Iraqi Journal of Veterinary Medicine, 2021)
Light and electron microscopic examinations were performed on kidneys of sheep infected with caseous lymphadenitis ( CLA ) caused by Corynebacterium pseudotuberculosis Membranproliferative glomerulonephritis was demonstrated. There were irregular thickenings of the glomeruelar basement membrane and glomerular cell proliferation, in contrast, no such lesions were found in the control lambs, indicating that CLA play a role in inducing glomerulorephritis